Respuesta :
Step-by-step explanation:
gradient(m)=change in y/change in x
=5-1/-9-(-4)
=4/-9+4
=4/-5
equation now
y-y1=m(x-x1)
y-1=4/-5[x-(-4)]
y=4/-5(x+4)+1
y=-4/5x-16/5+1
y=-4/5x-21/5
Answer:
y = -4/5x - 11/5
Step-by-step explanation:
First, find the slope using the slope formula.
[tex]m=\frac{y_1-y_2}{x_1-x_2}\\\\m=\frac{1-5}{-4-(-9)}\\\\m=-\frac{4}{5}[/tex]
Then, use the point-slope formula and substitute the values for the variables. I'll use (-4, 1) in this instance.
[tex]y-y_1=m(x-x_1)\\\\y-1=-\frac{4}{5}(x+4)\\\\y-1=-\frac{4}{5}x-\frac{16}{5}\\\\y=-\frac{4}{5}x-\frac{11}{5}[/tex]